Remastering Morals with Aristotle and Confucius - Sim, May (Cambridge University Press, 2013)
Melodrama is difficult to avoidwhen discussing the impact of Aristotle upon Western thought and practice and Confucius upon Asian thought and practice. Chinese culture is the single stem from which most East Asian cultures branch, and Master Kong is a taproot of these branches. Western cultures owe much to the Greek and Latin civilizations that styled Aristotle as the ‘‘master of those who know.’’ Each thinker’s prescription for life has influenced his traditions for millennia